2017
DOI: 10.1039/c6cs00465b
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-catalyzed cross-coupling reactions using organoindium reagents

Abstract: Transition metal-catalyzed cross-coupling reactions using organoindium reagents have witnessed rapid and comprehensive development in the past two decades. In comparison with many other organometallic reagents, the preparation of organoindium reagents and the subsequent transition metal-catalyzed cross-coupling reactions with various electrophiles showed a wider tolerance to important functional groups and protic solvents. In addition, in many cases, cross-coupling reactions employing organoindium reagents exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(49 citation statements)
references
References 49 publications
1
48
0
Order By: Relevance
“…Ethers are used to synthesise and stabilise the more reactive organometallics, including Grignard (organomagnesium) and Reformatsky (organozinc) reagents, as well as more exotic organoindium coupling partners. 63 Adamo et al found the choice of solvents available to them for a Suzuki reaction was limited by the solubility of 4cyanophenylboronic acid (which is soluble in DMF). 64 Protic solvents (e.g.…”
Section: Solvent Effects In Cross-coupling Reactionsmentioning
confidence: 99%
“…Ethers are used to synthesise and stabilise the more reactive organometallics, including Grignard (organomagnesium) and Reformatsky (organozinc) reagents, as well as more exotic organoindium coupling partners. 63 Adamo et al found the choice of solvents available to them for a Suzuki reaction was limited by the solubility of 4cyanophenylboronic acid (which is soluble in DMF). 64 Protic solvents (e.g.…”
Section: Solvent Effects In Cross-coupling Reactionsmentioning
confidence: 99%
“…The presence of halogens in the core of thiazole derivatives opens the door to using them as suitable substrates for coupling reactions and to expand the therapeutic potential of a compound by improving the pharmaceutical properties. Transition-metal-catalysed reactions constitute one of the most important and attractive research areas in academia, as well as in the pharmaceutical and fine chemical industries (Zhao et al, 2017;Jana et al, 2011). Cross-coupling reactions usually require, in addition to a transition metal, that the electrophilic coupling partner possesses leaving groups such as Br À or I À among others.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Although initially the term “cross-coupling” referred to the reaction of an organometallic reagent with an unsaturated organic halide or pseudohalide under transition metal catalysis, currently the definition is much more general and applies to reactions involving other components, conditions, and more complex synthetic transformations. In addition to the well-known and recognized cross-coupling reactions using organoboron (Suzuki-Miyaura), organotin (Stille), organozinc (Negishi), or organosilicon (Hiyama) nucleophiles, reactions involving other organometallic reagents such as organoindium [ 5 , 6 ], organolithium [ 7 ], and Grignard reagents [ 8 ] are now useful synthetic alternatives. Moreover, a wide range of carbon nucleophiles, from stabilized carbanions such as enolates and derivatives to neutral species, are also efficiently used [ 9 ].…”
mentioning
confidence: 99%